Perception of Professional Ethics and Awareness of Professional Ethical Principles of University Library Staff: Example of İzmir Universities - Akkaya, Mehmet Ali; Çağlar, Müge (Information World, 2025)
Ethics, which is accepted as one of the most effective tools of the process of change that transforms people into individuals and masses of people into society, is the expression of correct behavior patterns for institutions, professions and disciplines as well as individuals. The reflection of this identity in society is embodied through the principles shaped at the center of ethics. The necessity of ethics and ethical principles is much more evident in disciplines and professions that undertake direct roles in the adaptation of people to social life. One of the areas where this necessity is felt most intensely is the librarianship profession by its nature. In this study, it is aimed to reveal the perception of librarianship professional ethics and the opinions of the library employees working in the libraries of higher education institutions serving in Izmir regarding the necessity, comprehensibility, adequacy and usefulness of professional ethical principles. The integral goal of the research is to contribute to the importance of the subject to be on the agenda of the field by increasing the awareness of the library employees, who constitute the universe of the study, about professional ethics and professional ethical principles. In the study, a general evaluation was made considering the literature on ethics, professional ethics and the librarianship profession and ethical principles, and in the sections where the conceptual background was constructed, the descriptive method was used, and in revealing the perception of professional ethics and awareness of professional ethical principles of university library employees through the selected universe, the survey technique was used. Within the scope of the study, 53 of the 61 library employees who made up the universe were reached. The findings obtained revealed that the library employees who contributed to the research had dilemmas about librarianship ethics, and that their awareness on this issue was not fully adaptable to the pace of change in the profession, which strengthened these dilemmas. In the national literature, the ethics-library relationship, which is mostly addressed in public libraries due to the variety of users they serve, is usually selected as a research topic in the university library universe through a single university. The research, which addresses all 10 higher education institutions in Izmir, one of the largest cities in Turkey, in the context of librarianship-ethics convergence, stands at an original point in the literature in this respect.